Neurocognitive changes at different follow-up times after bilateral subthalamic nucleus deep brain stimulation in patients with Parkinson's disease - Wang, Zhuohang; Zheng, Zijian; Huang, Junwen; Cai, Xu; Liu, Xinjie; Xue, Cheng; Yao, Longping; Lu, Guohui (Heliyon, 2024)
Background - Bilateral deep thalamic nucleus brain stimulation (STN-DBS) surgery is often used to treat the motor symptoms of patients with Parkinson's disease. The change of neurocognitive symptoms in patients is, however, still unclear. - Objective - We aimed at analyzing the deterioration of neurocognitive symptoms in patients with Parkinson's disease after deep brain stimulation surgery under different follow-up times. - Methods - A comprehensive literature review was conducted using Pubmed, Cochrane Library, and Web of Science to screen eligible study records, the meta-analysis was performed using an inverse variance method and a random-effects model. Additionally, the areas of analysis include five: cognition, executive function, memory capacity, and verbal fluency (phonetic fluency and semantic fluency). They were analyzed for changes at six and twelve months postoperatively compared to baseline. The Meta-analysis has been registered with PROSPERO under the registration number: CRD42022308786. - Results - In terms of overall cognitive performance, executive function, and memory capacity, the original studies show a trend of improvement in these areas at 12 months postoperatively compared with 6 months, at variance, patients did not improve or deteriorated in phonetic fluency(d = −0.42 at both 6-month and 12-month follow-up) and semantic fluency from 6 to 12 months postoperatively. - Conclusion - In terms of most neurocognitive symptoms, including cognitive ability, executive function, and learning memory capacity, bilateral STN-DBS surgery appears to be safe at relatively long follow-up times. However, postoperative phonetic and semantic fluency changes should still not be underestimated, and clinicians should pay more attention to patients' changes in both.